Evaluation of OKRA (Abelmoschus esculentus) Macromolecular Solution for Enhanced Oil Recovery in Kazakhstan Carbonate Reservoir - Abbas, Azza Hashim; Ajunwa, Obinna Markraphael; Mazhit, Birzhan; Martyushev, Dmitriy A.; Bou-Hamdan, Kamel Fahmi; Alsaheb, Ramzi A. Abd (Energies (Basel), 2022)
Natural polymers have been investigated as part of the endeavors of green chemistry practice in the oil field. However, natural polymer studies are still preliminary. The current study examines okra’s (natural polymer) efficiency for polymer flooding, particularly in Kazakhstan. The evaluation targets the heavy oil trapped in carbonate reservoirs. SEM and FTIR were used to characterize morphology and chemical composition. A rheology study was conducted under different shear rates for three plausible concentrations: 1 wt.%, 2 wt.% and 5 wt.%. The core flooding was challenged by the low porosity and permeability of the core. The results showed that okra’s size is between 150–900 μm. The morphology can be described by rod-like structures with pores and staking as sheet structures. The FTIR confirmed that the solution contains a substantial amount of polysaccharides. During the rheology test, okra showed a proportional relationship between the concentration and viscosity increase, and an inversely proportional relationship with the shear rate. At reservoir temperature, the viscosity reduction was insignificant, which indicated good polymer stability. Okra showed shear-thinning behavior. It was fitted to the Ostwald–de Waele power-law model by a (90–99)% regression coefficient. The findings confirm okra’s pseudo-plasticity, and that it is proportional to the solution concentration. The incremental oil recovery was 7%. The flow was found to be restricted due to the mechanical entrapment resulting from the large molecule size and the low porosity–permeability of the system. This study proves that the dominating feature of natural polysaccharide derivatives is their applicability to moderate reservoir conditions. The current study is a positive attempt at natural polymer application in Kazakhstan and similar field conditions.